Impact of Macroeconomic and Financial Determinants on Share Prices in Pakistan’s Islamic Banking Sector - Siddiqui, Arsalan Ahmed; Dr. Muhammad Muzammil (Dialogue Social Science Review (DSSR), 2025)
This thesis investigates the various factors influencing the share prices of Islamic banks in Pakistan, a sector that has experienced significant growth since its formal introduction in 2002. Rooted in Sharia principles prohibiting interest (Riba) and emphasizing ethical practices and risk-sharing, Islamic banking has become an essential component of Pakistan's financial system, contributing to both financial inclusion and economic stability. Despite its rapid expansion, the industry continues to face challenges, including limited consumer awareness and a narrow range of financial products, indicating potential for further development. The study examines how external macroeconomic variables—such as inflation, exchange rates, conventional interest rates, and GDP—and internal financial indicators—including Return on Equity (ROE), Earnings Per Share (EPS), Price-to-Earnings (P/E) ratio, asset growth, and payout ratio—affect the share prices of three Islamic banks operating in Pakistan. Covering the years 2019 to 2023, the research utilizes secondary time-series data sourced from official records, including reports from the State Bank of Pakistan (SBP), the Pakistan Bureau of Statistics (PBS), and the banks’ own annual statements, with data analysis performed using EViews software through descriptive and correlation-based methods. The results highlight a strong connection between macroeconomic changes and the performance of Islamic bank shares. For instance, the depreciation of the Pakistani Rupee and rising inflation in the latter part of the study period had noticeable effects on investor behavior and bank profitability. Additionally, shifts in GDP and conventional interest rates—despite being prohibited under Islamic finance—still played an indirect role in shaping market perceptions. On the internal side, improvements in EPS and asset growth were generally linked to rising share prices, indicating better financial health. In contrast, a falling P/E ratio and changes in payout policies often pointed to wavering investor confidence or shifts in how banks managed their capital. Overall, the research provides valuable insight into how a combination of external economic conditions and internal financial performance shapes the valuation of Islamic banks in Pakistan’s ever-changing financial environment.